ATF3 Regulates the Expression of AChE During Stress - Heinrich, Ronit; Hertz, Rivka; Zemel, Esther; Mann, Irit; Brenner, Liat; Massarweh, Amir; Berlin, Shai; Perlman, Ido (Frontiers in Molecular Neuroscience, 2018)
Acetylcholinesterase (AChE) expresses in non-cholinergic cells, but its role(s) there remain unknown. We previously attribute a pro-apoptotic role for AChE in stressed retinal photoreceptors by unknown mechanism. Here, we examined its promoter only to find that it includes a binding sequence of the Activating Transcription Factor 3 (ATF3); a prototypical mediator of apoptosis. This suggests that expression of AChE could be regulated by ATF3 in the retina. Indeed, ATF3 binds the AChE-promoter to down-regulate its expressions in vitro. Strikingly, retinas of ‘blinded’ mice display apoptosis hallmarks, almost exclusively in the outer nuclear layer; coinciding with elevated levels of AChE and absence of ATF3. A mirror image is observed in the inner nuclear layer, namely prominent levels of ATF3 and lack of AChE and apoptosis. We conclude that segregated patterns of expressions of ATF3 reflect its ability to repress apoptosis in different layers of the retina—a novel mechanism behind apoptosis.